Selecting score types for longitudinal evaluations: the responsiveness of the Comprehensive Developmental Inventory for Infants and Toddlers in children with developmental disabilities - Tsai Y; Tung L; Lee Y; Wang Y; Yen Y; Chen K (Neuropsychiatric Disease and Treatment)
Yu-Pei Tsai,1,2 Li-Chen Tung,1,3 Ya-Chen Lee,4 Yu-Lin Wang,1,5 Yun-Shan Yen,1 Kuan-Lin Chen4,6 1Department of Physical Medicine and Rehabilitation, Chi-Mei Medical Center, Tainan, 2Department of Special Education, National Chiayi University, Chiayi, 3School of Medicine, Chung Shan Medical University, Taichung, 4Department of Occupational Therapy, College of Medicine, National Cheng Kung University, 5Department of Sports Management, Chia Nan University of Pharmacy and Science, 6Department of Physical Medicine and Rehabilitation, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, Taiwan Objective: The objective of this study was to examine the responsiveness of the Comprehensive Developmental Inventory for Infants and Toddlers (CDIIT) in children with developmental disabilities (DD).Methods: The responsiveness of a measure is its ability to detect change over time, and it is fundamental to an outcome measure for detecting changes over time. We compared the responsiveness of four types of scores (ie, raw scores, developmental ages [DAs], percentile ranks [PRs], and developmental quotients [DQs]) in the five subtests of the CDIIT. The CDIIT was administrated three times at intervals of 3 months on 32 children with DD aged between 5 months and 64 months (mean =30.6, standard deviation [SD] =17.8). The CDIIT is a pediatric norm-referenced assessment commonly used for clinical diagnosis of developmental delays in five developmental areas: cognition, language, motor, social, and self-care skills. The responsiveness was analyzed using three methods: effect size, standardized response mean, and paired t-test.Results: The effect size results showed that at the 3-month and 6-month follow-ups, responsiveness was small or moderate in the raw scores and DAs of most of the subtest scores of the CDIIT, but the level of responsiveness varied in the PRs and DQs. The standardized response mean results of the 3-month and 6-month follow-ups showed that most of the subtest scores of the CDIIT had respectively moderate and large responsiveness in raw scores and DAs, but the responsiveness varied (from no to large) in PRs and DQs.Conclusion: The findings generally support the use of the CDIIT as an outcome measure. We also suggest using the raw scores and DAs when using a norm-referenced pediatric developmental assessment to evaluate developmental changes and program effectiveness in children with DD. Keywords: responsiveness, developmental assessment, developmental disabilities